Repellence Produced by Monoterpenes on Rhodnius prolixus (Hemiptera: Reduviidae) Decreases After Continuous Exposure to These Compounds - Lutz, Alejandra (2014)
Botanical monoterpenes are secondary metabolites present in essential oils produced by plants. Some of them are insect repellents. The bloodsucking bug Rhodnius prolixus Ståhl (Hemiptera: Reduviidae) is one of the main vectors of Chagas disease in the north of South America and some countries in Central America. In this study, we studied the repellence produced by two monoterpenes, menthyl acetate and geraniol, on fifth instar nymphs of R. prolixus. In the absence of other stimuli, both menthyl acetate and geraniol produced a repellent effect from 740 μg/cm² and 74 μg/cm², respectively. Pre-exposure to each monoterpene reduced the repellent activity produced by the same substance. Additionally, pre-exposure to one monoterpene decreased the behavioral response of the nymphs to the other one. The repellent effect of both monoterpenes also decreased when nymphs' antennae were previously treated with the nitric oxide donor S-nitroso-N-acetyl-cysteine.